2013
DOI: 10.1111/ane.12124
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Epstein-Barr virus infection in Chinese myasthenia gravis patients

Abstract: Our results therefore do not support a role of thymic Epstein-Barr virus infection in myasthenia gravis pathogenesis and calls for an integration of methodological and interpretation issues in detecting Epstein-Barr virus incidence in myasthenia gravis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…EBV is one of the most concerning viruses in the literature regarding the correlation between viruses and MG with thymus abnormalities, but the role of EBV in the pathogenesis of MG remains controversial. 6 - 10 Thus, in this study, we mainly explored the role of B19V, a virus playing a similar role to EBV in autoimmune diseases, in thymoma, and further investigated EBV status. B19V was first discovered by Cossart et al in 1975.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBV is one of the most concerning viruses in the literature regarding the correlation between viruses and MG with thymus abnormalities, but the role of EBV in the pathogenesis of MG remains controversial. 6 - 10 Thus, in this study, we mainly explored the role of B19V, a virus playing a similar role to EBV in autoimmune diseases, in thymoma, and further investigated EBV status. B19V was first discovered by Cossart et al in 1975.…”
Section: Discussionmentioning
confidence: 99%
“…In general, chronic inflammation of the thymus caused by a viral or bacterial infection may trigger the development of autoimmunity, generally by activating the host immune system and molecular mimicry, thereby contributing to the pathogenesis of MG. Some studies have demonstrated that intrathymus Epstein–Barr virus (EBV) infection is an environmental risk factor for MG. 6 , 7 However, an increasing number of studies have reported a lack of evidence for EBV infection in the thymus of patients with MG. 8 - 10 Hence, the role of EBV in the pathogenesis of MG remains controversial.…”
mentioning
confidence: 99%
“…assessedNo. positive1988McGuire et al [13]ChinaSBHT, LT, TIMG1161990Inghirami et al [14]USA, ItalySBH, PCRTMG1601990Borisch et al [15]GermanyISH, SBHNT, THMG5101992Mann et al [16]USAISHLT, T/TC40/70/11993Wu et al [17]ChinaISHT/TC21/200/11993Fujii et al [18]JapanISHT/TC7/80/12000Hishima et al [19]JapanISHT/TC18/902000Engel et al [20]DenmarkISHT/TC105/5202001Tateyama et al [21]JapanISHT/TC9/24/12002Chen et al [22]ChinaISH, PCRT/TC78/210/62010Cavalcante et al [6]ItalyISH, IH, PCRTH, LT, TIMG17172011Meyer et al [8]GermanyISH, IHLTMG4402011Cavalcante et al [7]ItalyPCRTH, LT, TIMG19122011Kakalacheva et al [9]EuropeISH, IH, PCRLTMG1612013Jing et al [23]ChinaISH,...…”
Section: Resultsmentioning
confidence: 99%
“…The EBVinduced TLR7/9 signaling pathway-mediated immune response might play a role in the progression of MG [54]. However, Meyer et al and Jing et al reported no evidence of EBV association with MG thymus contradicting the previous studies [55,56]. Other studies also indicate the role of cytomegalovirus, human foamy virus (HFV), and Nile virus in the progression of MG [33,57].…”
Section: Etiological Factors and Pathophysiologymentioning
confidence: 95%